An Exploratory Study on the Application of Lean Management and Six Sigma in a Malaysian based Haulage Company - Tai, Kin Tat (2010)
This paper presents a study on the operational improvement using Lean Management and Six Sigma in a logistics company, specifically in the haulage division. The company in focus is a pioneer logistics company in Malaysia, facing intense competition from new startups since the national liberalisation of the haulage industry. In order to stop their dwindling market share from being taken by new container hauliers, the company strives to improve their haulage operation which is their core business. The research would analyse the haulage operations from the Lean Management and six sigma perspective. A lean operation is achieved by first identifying what is value adding and non-value adding processes in the supply chain. Processes that do not add value is called waste and it should be eliminated or minimized. Six Sigma focuses on the reduction of variation in a process. Since Six Sigma is a data driven decision making methodology, some statistical analysis is required. Though Lean Management and Six Sigma are methodologies which found their roots from the manufacturing environment, there has been a growing trend that these methodologies are being adopted beyond the shop floor. This project takes Lean Management and Six Sigma into a new field. The haulage operation was analysed based on these methodology and the project’s findings revealed that the company could improve their competitive advantage if the proposed 10 recommendations are implemented.